PERAN MANAJEMEN PENGAWASAN DI PERUSAHAAN KOTA CILEGON DALAM MENINGKATKAN KAPABILITAS KARYAWAN - Putra, Arta Rusidarma; Silfiana, Silfiana (Bhinneka Multidisiplin Journal, 2024)
In a company, the existence of quality Supervisory Management is vital to overseeing company operations. This management is a reference for assessing the quality of a company, especially when the majority of ownership is the State. Therefore, good corporate governance is the key to ensuring the company's positive contribution, involving employee morale, planning and ability to respond. This research method uses a qualitative approach and evaluates previous research that is relevant to the topic of discussion. This article reviews "Planning and implementation of supervisory management is influenced by employee commitment, planning and ability." This article aims to formulate a hypothesis regarding the relationship of these variables in the context of human resource management. The results of the literature study show that employee commitment, planning and ability each have a positive impact on supervisory management